Assessing PDL-1 and PD-1 in NoneSmall Cell Lung Cancer: A Novel Immunoscore Approach - Paulsen, Erna-Elise; Kilvær, Thomas Karsten; Rakaee, Mehrdad; Al-Saad, Samer; Hald, Sigurd; Andersen, Sigve; Richardsen, Elin; Ness, Nora; Busund, Lill-Tove; Bremnes, Roy M.; Dønnem, Tom (Clinical Lung Cancer, 2016)
Published version. Source at http://dx.doi.org/10.1016/j.cllc.2016.09.009 Novel immune biomarkers could complement the TNM classification for nonesmall cell cancer (NSCLC), improving the prognostic accuracy. The present study evaluated the prognostic significance of the immune checkpoint molecules programmed cell death protein 1 (PD-1) and PD-1 ligand (PD-L1) in 536 patients with stage I to IIIA NSCLC using an Immunoscore approach. Independently, and in combination, the infiltration of immune cells expressing PD-L1 and PD-1 predicted patient survival, supplementing the TNM classification in each stage. Introduction: Immune checkpoint inhibitors targeting programmed cell death protein 1 (PD-1) or its ligand, PD-L1, have gained momentum in the treatment of nonesmall cell lung cancer (NSCLC). However, their prognostic significance remains controversial. The present study evaluated the expression of PD-L1 and PD-1 and their potential role in an Immunoscore, supplementing the TNM classification of NSCLC. Materials and Methods: Tissue microarrays constructed from tumor tissue samples from 2 cohorts of a total of 536 patients (University Hospital of North Norway, n ¼ 285; Nordland Hospital, n ¼ 251) with primary resected stage I to IIIA NSCLC. PD-L1 and PD-1 were evaluated by immunohistochemistry in the primary tumor and metastatic lymph node tissue. Results: In univariate analysis, a high density of PD-L1þ immune cells in the stromal compartment (S-PD-L1) and PD-1þ intraepithelial tumor infiltrating lymphocytes (T-PD-1) was associated with favorable disease-specific survival (DSS; S-PD-L1, P ¼ .004; T-PD-1, P ¼ .012), both limited to the squamous cell carcinoma histologic subgroup (S-PD-L1, P ¼ .002; T-PD-1, P ¼ .034). A combined low S-PD-L1 and T-PD-1 was associated with poor survival in all patients (DSS: hazard ratio [HR], 1.81; 95% confidence interval [CI], 1.37-2.40; P < .001) at both centers and for all pathologic stages. In multivariate analysis, S-PD-L1 and T-PD-1 were independent positive prognostic ...